2016
DOI: 10.1039/c6pp00048g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-induced multicolour fluorescence of amino-substituted 2,3-naphthalimides studied by fluorescence and transient absorption measurements

Abstract: A series of amino-2,3-naphthalimide derivatives having the amino functionality at 1-, 5- and 6-positions (, and , respectively) were prepared, and their photophysical properties were systematically investigated based on the measurements of steady-state absorption and fluorescence spectra, fluorescence lifetimes as well as transient absorption spectra. The s efficiently fluoresced in solution, and the emission spectra appreciably shifted depending on the solvent polarity. displayed only a slight fluorescence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…ESIPT is a process in which the excited state is relaxed by the structural relaxation (tautomerization) from the normal (N*) form to the tautomer (T*) form, through proton transfer in the excited state, resulting in a large energy gap between the absorption and emission, leading to a very large ν. In particular, the ESIPT occurring at amino (-NH 2 ) or substituted amino (-NHR) groups undergo more efficient proton transfer than that of the hydroxy (-OH) group, and its ESIPT reaction can be controlled by the electronegativity of the substituents [37][38][39][40]. To achieve white light with ESIPT, it is necessary to design molecules which emit yellow fluorescence via ESIPT (the emission wavelength should be around 550-580 nm) [41].…”
Section: Introductionmentioning
confidence: 99%
“…ESIPT is a process in which the excited state is relaxed by the structural relaxation (tautomerization) from the normal (N*) form to the tautomer (T*) form, through proton transfer in the excited state, resulting in a large energy gap between the absorption and emission, leading to a very large ν. In particular, the ESIPT occurring at amino (-NH 2 ) or substituted amino (-NHR) groups undergo more efficient proton transfer than that of the hydroxy (-OH) group, and its ESIPT reaction can be controlled by the electronegativity of the substituents [37][38][39][40]. To achieve white light with ESIPT, it is necessary to design molecules which emit yellow fluorescence via ESIPT (the emission wavelength should be around 550-580 nm) [41].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the microenvironment solvent polarity significantly influenced the fluorescence position, which may attribute to hydrogen bonding interactions between the tertiary amine chromophore and polar protic solvent. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…With our two communications among the first reported N -aryl-2,3-napthalimides panchromatic fluorescent dyes, the considerable number of citations prompted us to expand these photoluminescent solvent studies to electroluminescent WOLEDs. , Since those early entries, relatively few small-molecule dyes have been reported to display white light emission. The widely used approach for a single chromophore to achieve white electroluminescence is taken via short-wavelength fluorescence from the electron–hole recombination in an individual molecule and the broad longer-wavelength fluorescence from the intermolecular interactions. The intermolecular interactions usually originate from the formation of excimers, electromers, and aggregates .…”
Section: Resultsmentioning
confidence: 99%